ANALISIS KEBUTUHAN TENAGA REKAM MEDIS DI BAGIAN PENDAFTARAN DI RUMAH SAKIT UMUM DAERAH AMBARAWA - Sugiyanto .; Sri Lestari; Widodo . (Jurnal Manajemen Informasi Kesehatan Indonesia (JMIKI), 2017)
Ambarawa General Hospital (RSUD) has 8 counters consisting of 2 General counters, 1 Jamkesmas, and 5 BPJS counters, with 7 TPPRJ personnel divided into 2 at General Counter, 1 as Jamkesmas counter staff, and 4 BPJS counter officers. Every patient who comes to the hospital  gets  a  queuing  number  corresponds  to  the  patient’s   need. It is discovered that there are queues at the registration section and many patients complain for a long line, therefore the conformity between the number of personnel based on queuing system is needed at TPPRJ RSUD Ambarawa.The type of this research is qualitative,  with observational research methods descriptive survey approach. The dependent variable is the manpower needed at the TPPRJ Section of RSUD Ambarawa on 2016. Whereas the independent variables are queue, number of counters, number of officers, and job description at TPPRJ area.Based on the observation, it shows that the arrival rate of patient for BPJS counter is 65 patients per hour. While the service rate of patient is 30 patients per hour for BPJS counter. By using WIN QSB program, it is understood that the number of patients on BPJS counter queue is by 1   person.   There   are   8   counters   available;   2   general     counters, 1 Jamkesmas, and 5 BPJS counters which are manned by 4 personnel. Thus,   it   is   acknowledged   that   1   personnel   addition   is   needed to be assigned at the available BPJS counter in order to avoid patients queue congestion as well as to accelerate patient’s registration. It is also understood that the addition of 3 officers is required for the BPJS outpatient’s registration. This should be carried out because on the accreditation, the number of staff should be equal to the number of counters available